1997
DOI: 10.1021/ma970989i
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity-Induced Biodegradation of Novel [(R,S)-β-Butyrolactone]-b-pivalolactone Copolymers

Abstract: Novel model block copolymers of (R,S)-β-butyrolactone with pivalolactone (PVL) are prepared in order to define the effect of crystalline domains provided by poly(pivalolactone) on the biodegradability of atactic poly(β-butyrolactone), a-PHB. The “living” a-PHB is synthesized from racemic β-butyrolactone, in the presence of potassium alkoxide/18-crown-6 complex, and such a living polymer is applied for polymerization of PVL, yielding block copolymers, a-PHB-b-PPVL, of tailored molecular weight and composition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 38 publications
5
46
0
3
Order By: Relevance
“…With further increasing the 3MP unit content, however, another crucial process, i.e., adsorption of enzyme on the surface of polyesters, should be taken into consideration, with noting only crystalline phase can provide a binding support to the enzyme. 23,24 It is expected that the amount of the enzyme adsorbed on subtract surface will decrease with the crystallinity. Crystallnity / %…”
Section: Resultsmentioning
confidence: 99%
“…With further increasing the 3MP unit content, however, another crucial process, i.e., adsorption of enzyme on the surface of polyesters, should be taken into consideration, with noting only crystalline phase can provide a binding support to the enzyme. 23,24 It is expected that the amount of the enzyme adsorbed on subtract surface will decrease with the crystallinity. Crystallnity / %…”
Section: Resultsmentioning
confidence: 99%
“…Scandola et al reported that a-P(3HB) was biodegraded in binary blends with natural poly(3-hydroxybutyrate-co-3hydroxyvalerate) (P(3HB-3HV), [14] poly-(e-caprolactone) (PCL) and poly(l-lactic acid) (PLLA), [15] and in di-block copolymer with poly(pivalolactone) (PPVL). [16] It is noteworthy that PCL, PLLA and PPVL are not degraded by the P((R)-3HB) depolymerases, but they are biodegradable polymers such as P((R)-3HB) and P(3HB-3HV). The phenomenon that a-P(3HB) segments are not biodegraded alone but biodegraded in the blends or in the diblock copolymer by the P((R)-3HB) depolymerase is very interesting and is called as crystalline-induced biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon that a-P(3HB) segments are not biodegraded alone but biodegraded in the blends or in the diblock copolymer by the P((R)-3HB) depolymerase is very interesting and is called as crystalline-induced biodegradation. [16] Analyses of the structural genes of the P((R)-3HB) depolymerases have revealed that these enzymes are organized with two domains and a linker region. [10,17,18] One of the two domains, the substrate binding domain, plays a role in binding to the P((R)-3HB) surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar induced biodegradation has been also observed for chemosynthetic [(R,S)-{3-butyrolactone]-b-pivalolactone copolymers. 38 The similar case may also occur in the AB and CB blends.…”
Section: Enzymatic Degradationmentioning
confidence: 76%